PERSISTENSI LABA DITINJAU DARI KOMPONEN PEMBENTUK LABA - Utami, Tri (KIAT BISNIS, 2016)
Earning persistence influenced by the components of its own earnings, accruals and cash which negative or positive, if itâs positive will be distributed to dividends, buy more share, pay debts and interest, and also financial assets increase. If negative, the company must be efficient, such as adding capital funds, debt or reduce cash owned. Previous research tested the persistence of the accrual and cash income components but was not specific because without looking at the composition, specific testing to determine the persistence level of free cash flow, the result of the accrual earnings component and the less persistent cash. This research proposes a hypothesis that free cash flow components held by the firm will show a lower persistence than the distributed free cash flow component. A positive free cash flow can be distributed to shareholders in the form of dividend payments or to buy shares again. So, free cash flow of shareholders will be more persistent than free cash flows which distributed to creditors. We used secondary data on this research which can be obtained from OSIRIS database. This research gets sample from all companies that have been listed on the Stock Exchange, and year of observation between 2006-2015. Research variable use the income variable, where the income itself consists of accruals and free cash flow. The results indicate that the free cash flow component is dominated by free cash flows retained rather than the free cash flow which distributed. Keywords: earnings persistence, free cash flow, cash, accrual